Memaknai Ruang Dalam Fotografi Jalanan “Home Street Home” - sebastianus advent (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
This study attempted to analyze and interpret about “space” trough photography, particularly a street photography. Public space is a place where people meet each other, interact, communicate, earn a living, do politics, and there are still many activities carried out in public space. How important public space for some people who depend on their lives in public space. In other word, human can live, without disturbing their privacy space. Home Street Home is a smallest piece of absorptive public space through photography. In this study, the writer also attempted to explain about how photography sees public space as a picture of human define the public space as their private space either. Public as a home is considered to be most comfortable and intimate place. Home is not a space that literally roofed, protect human from rain, shade, and comfort. But home is an intimate space, a place where human returns to get back their humanity, and become a privacy space.